Towards green growth: monitoring progress. OECD indicators (Paris, 2011)
"This book provides measurement tools, including indicators, to support countries’ efforts to achieve economic growth and development, while ensuring that natural assets continue to provide the resources and environmental services on which well-being relies. The strategy proposes a flexible policy framework that can be tailored to different country circumstances and stages of development. This report accompanies the synthesis report Towards Green Growth. "